Rocket Measurement of Auroral keV Electron Fluxes in Antarctica - Kaya, Nobuyuki; Matsumoto, Haruya; Yamagishi, Hisao (1981)
P(論文) Electron fluxes in auroras were observed with an electron spectrometer (ESM) onboard Japanese Antarctic sounding rockets S-310JA-5 and -6 at Syowa Station. Both rockets successfully penetrated into auroras, each different kind, respectively. The ESM worked successfully and measured the energy spectra and pitch angle distributions of precipitating and upgoing electrons. Electron fluxes of (10)^7∿(10)^9(/(cm)^2・sr・s・keV) were observed in the energy range from 1 to 10keV. In the S-310JA-5 rocket experiment, there were peaks at 2keV in the energy spectra of the downward electron flux on the both edges of the auroral arcs and those of 4.5keV inside of the auroral arcs. The result showed energy spectra of the inverted V shape. The electron fluxes with small pitch angles were higher than those with large pitch angles. The upgoing fluxes are generally lower than the precipitating fluxes. The flux difference strongly depends on the energy and rocket altitudes. In the S-310JA-6 rocket experiment, the spectral peaks were not observed, and intensities of electron fluxes of several keV showed a good correlation with an appearance of bright auroral arcs in the all-sky camera photographs. The down-going fluxes are almost isotropic in pitch angles for all energy ranges and all altitudes. departmental bulletin paper